EXTENSION OF NASH EQUILIBRIUM THEOREMS USING SOFT SET - C.WARRIER, SREELEKSHMI (International Journal of Mathematical Archive, 2018)
John Nash describing Nash equilibrium using Brower’s and Kakutani’s fixed point theorems. Molodstov initiated the soft set theory which also deals with decision making under uncertainty. Here we extend some of the theorems on Nash equilibrium related to fixed point theory using soft set approach.